Effects of a hard stop for C. difficile testing: Provider uptake and patient outcomes - Danielle Doughman; David Weber; Nikolaos Mavrogiorgos; Shelley Summerlin-Long; Michael Swartwood; Alexander Commanday; Lisa Stancill; Nicholas Kane; Emily Sickbert-Bennett Vavalle (Cambridge University Press, 2023)
Background: Clostridioides difficile infection (CDI) is a serious healthcare-associated infection responsible for >12,000 US deaths annually. Overtesting can lead to antibiotic overuse and potential patient harm when patients are colonized with C. difficile, but not infected, yet treated. National guidelines recommend when testing is appropriate; occasionally, guideline-noncompliant testing (GNCT) may be warranted. A multidisciplinary group at UNC Medical Center (UNCMC) including the antimicrobial stewardship program (ASP) used a best-practice alert in 2020 to improve diagnostic stewardship, to no effect. Evidence supports use of hard stops for this purpose, though less is known about provider acceptance. Methods: Beginning in May 2022, UNCMC implemented a hard stop in its electronic medical record system (EMR) for C. difficile GNCT orders, with exceptions to be approved by an ASP attending physician. Requests were retrospectively reviewed May-November 2022 to monitor for adverse patient outcomes and provider hard-stop compliance. The team exported data from the EMR (Epic Systems) and generated descriptive statistics in Microsoft Excel. Results: There were 85 GNCT orders during the study period. Most tests (62%) were reviewed by the ASP, and 38% sought non-ASP or no approval. Of the tests reviewed by the ASP, 33 (62%) were approved and 20 (38%) were not. Among tests not approved by the ASP, no patients subsequently received CDI-directed antibiotics, and 1 patient (5%) warranted same-admission CDI testing (negative). Of tests that circumvented ASP review, 18 (56%) ordering providers received a follow-up email from an associate chief medical officer to determine the rationale. No single response type dominated: 3 (17%) were unaware of the ASP review requirement, 2 (11%) indicated their patient's uncharted refusal of laxatives, 2 (11%) indicated another patient-specific reason. Provider avoidance of the ASP approval mechanism decreased 38%, from 53% of noncompliant tests in month 1 to 33% of tests in month 6. Total tests orders dropped 15.5% from 1,129 during the same period in 2021 to 954 during the study period (95% CI, 13.4%-17.7%). Compliance with the guideline component requiring at least a 48-hour laxative-free interval prior to CDI testing increased from 85% (95% CI, 83%-87%) to 95% (95% CI, 93%-96%). CDI incidence rates decreased from 0.52 per 1,000 patient days (95% CI, 0.41-0.65) to 0.41 (95% CI, 0.32-0.53), though the change was neither significant at P = .05 nor attributable to any 1 intervention. Conclusions: Over time and with feedback to providers circumventing the exception process, providers accepted and used the hard stop, improving diagnostic stewardship and avoiding unneeded treatment.